The Effect of Corporate Social Responsibility, Good Corporate Governance, Free Cash Flow, Leverage, and Profitability on Earnings Management in Industrial Sector Companies Listed on the Indonesia Stock Exchange - Wike Sabina Sinulingga; Milka Arfina Saragih; Annisa Nauli Sinaga; Mitha Christina Ginting (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study aims to analyze whether Corporate Social Responsibility, Good Corporate Governance, Free Cash Flow, Leverage, and Profitability have an influence on earnings management. This study was conducted on industrial companies listed on the Indonesia Stock Exchange for the 2022-2024 period, with a research population of ninety four (94) companies listed on the Indonesia Stock Exchange. The sampling technique used a purposive sampling technique, resulting in a sample of sixty one (61) companies. The data used were the financial reports of each sample company published on www.idx.co.id. The research method used was a descriptive method, classical assumption tests, and multiple linear regression analysis using the SPSS program. The results of the study indicate that partially, Free Cash Flow and Leverage have a significant effect on earnings management. Meanwhile, CSR, GCG, and Profitability have no significant effect on earnings management. This study is expected to serve as a reference for investors and further researchers in understanding the factors that influence earnings management.